2016
DOI: 10.1111/appy.12243
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent self‐harm and risk factors

Abstract: The incidence of adolescent self-harm was high, and their mental health status, stressful life events, and EMBU affected the occurrence of adolescent self-harm, which is an issue that needs greater attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 34 publications
1
26
0
8
Order By: Relevance
“…To understand the mechanism that causes the best electrochemical performance of LVO‐15 among all samples, we measured the surface energies of the samples using an inverse gas chromatography (IGC) method . The dispersive surface energy was determined by the n ‐hexane, n ‐heptane, n ‐octane and n ‐nonane probes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism that causes the best electrochemical performance of LVO‐15 among all samples, we measured the surface energies of the samples using an inverse gas chromatography (IGC) method . The dispersive surface energy was determined by the n ‐hexane, n ‐heptane, n ‐octane and n ‐nonane probes.…”
Section: Resultsmentioning
confidence: 99%
“…The monopolar probes, dichloromethane and ethyl acetate, were also injected in order to obtain the acid‐base surface energy. However, the analyzed materials had strong interactions with those probes; thus no elution was detected …”
Section: Methodsmentioning
confidence: 99%
“…Our results indicated that family life stress events were significantly associated with SH but not with highly lethal self-harm in Chinese adolescents. Contradictory findings have reported that the number of negative life events in the previous year increased not only the risk of NSSI [ 46 ] but also suicide attempts [ 47 ]. Indeed, negative life events experiences may influence the stress system by altering stress systems, such as influencing individuals’ hormones and neurotransmitters, and the subsequent imbalance may lead to suicidal behaviour [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the theoretical stimulation calculation of Li 3 VO 4 crystal, the volume expansion is only ∼4 % when x=2 in Li 3+x VO 4 . Apart from all these merits, Li 3 VO 4 has an intrinsic shortcoming of low electronic conductivity which may lead to large resistance polarization and poor rate capability . To overcome this weakness, extensive researches have been carried out to prepare the composites based on LVO, such as carbon‐encapsulated Li 3 VO 4 particles, Li 3 VO 4 /N doped C, Li 3 VO 4 /graphene,, Li 3 VO 4 /expanded graphite and Li 3 VO 4 /carbon nanotubes (CNTs) .…”
Section: Introductionmentioning
confidence: 99%